EDUKASI SERTA PELATIHAN PENGOLAHAN MINYAK JELANTAH MENJADI SABUN CUCI DI KECAMATAN MANTINGAN KABUPATEN NGAWI JAWA TIMUR - Rizki Awaluddin; Solikah Ana Estikomah; Satwika Budi Sawitri (Jurnal Abdi Insani, 2022)
Used cooking oil is used cooking oil. Used cooking oil that is used repeatedly can cause disease, in addition, if it is disposed of directly into the environment, it can cause environmental pollution. The lack of public knowledge about the dangers of using used cooking oil will eventually have a negative impact, so there is a need for public education about the health risks of using used cooking oil and the need for training to recycle used cooking oil to make products that are beneficial and friendly to the environment. The purpose of this activity is to educate and provide skills through training provided to the community, especially PKK women in Sambirejo village about processing used cooking oil into solid soap. The method in community service is in the form of counseling accompanied by questions and answers, then demonstrations and practice are carried out. The material presented in the counseling was the understanding of used cooking oil and the dangers of consuming it, the impact of throwing waste directly into the ground/water, and how to recycle used cooking oil. Based on the results of the program implementation, it was found that making soap from used cooking oil was easily understood by partners from PKK women from Sambirejo Mantingan village. The sustainability of this program deserves to be maintained in order to increase the independence of the community through the manufacture of economically valuable products. Community empowerment through making soap from used cooking oil as an effort to provide benefits to the community. Making soap from used cooking oil is easily understood by partners.